The Psychology of Rituals: An Integrative Review and Process-Based Framework - Hobson, Nicholas M.; Schroeder, Juliana; Risen, Jane L.; Xygalatas, Dimitris; Inzlicht, Michael (Personality and social psychology review, 2018)
Traditionally, ritual has been studied from broad sociocultural perspectives, with little consideration of the psychological processes at play. Recently, however, psychologists have begun turning their attention to the study of ritual, uncovering the causal mechanisms driving this universal aspect of human behavior. With growing interest in the psychology of ritual, this article provides an organizing framework to understand recent empirical work from social psychology, cognitive science, anthropology, behavioral economics, and neuroscience. Our framework focuses on three primary regulatory functions of rituals: regulation of (a) emotions, (b) performance goal states, and (c) social connection. We examine the possible mechanisms underlying each function by considering the bottom-up processes that emerge from the physical features of rituals and top-down processes that emerge from the psychological meaning of rituals. Our framework, by appreciating the value of psychological theory, generates novel predictions and enriches our understanding of ritual and human behavior more broadly.